Cold sintering: Current status and prospects - Maria, Jon-Paul; Kang, Xiaoyu; Floyd, Richard D.; Dickey, Elizabeth C.; Guo, Hanzheng; Guo, Jing; Baker, Amanda; Funihashi, Shuichi; Randall, Clive A. (Journal of materials research, 2017)
This manuscript describes, defines, and discusses the process of cold sintering, which can consolidate a broad set of inorganic powders between room temperature and 300 °C using a standard uniaxial press and die. This temperature range is well below that needed for appreciable bulk diffusion, indicating immediately the distinction from the well-known and thermally driven analogue, allowing for an unconventional method for densifying these inorganic powders. Sections of this report highlight the general background and history of cold sintering, the current set of known compositions that exhibit compatibility with this process, the basic experimental techniques, the current understanding of physical mechanisms necessary for densification, and finally opportunities and challenges to expand the method more generically to other systems. The newness of this approach and the potential for revolutionary impact on traditional methods of powder-based processing warrants this discussion despite a nascent understanding of the operative mechanisms.